PENGARUH VARIASI JUMLAH AGREGAT PADA CAMPURAN BETON (MIX DESIGN) TERHADAP KUAT TEKAN BETON - Teuku Budi Aulia (JURNAL TEKNIK SIPIL, 2012)
Abstract: This research aims to know the influence of the percentage of aggregate amount against the normal concrete compressive strength with a Water Cement Ratio (w/c-ratio) of 0.35; 0.40 and 0.45, in order to obtain the optimum percentage of aggregate amount in the concrete mix. The specimens used in this research were the standard cylinders with a diameter of 150 mm and a height of 300 mm amounting to 90 samples and cubes with a size of 150 x 150 x 150 mm amounting to 54 samples. The maximum aggregate diameter was 25.4 mm with the planned slump of 75-100 mm. Variables in this study were three variations of w/c-ratio and three variations of the percentage of aggregate amount (60%; 70% and 80%). Concrete compression tests were carried out at the age of 7 and 28 days using the compression tester machine with a capacity of 100 ton. The standards used in this research were the American Concrete Institute (ACI), the American Society for Testing and Materials (ASTM), British Standard (BS), and the Indonesia National Standard (SNI). Concrete mix design was done by the method of weight proportion of the material. Cement being used was Portland Cement Type I. To record the data of loads and deformations during testing was used portable data logger. To analyze the effect between determined variables was selected a variant analysis using two ways classification with fixed effect model. Regression analysis used was multiple polynomial regression. Based on the variance analysis results, it is showed that there is a significant influence between the aggregate amount against the concrete compressive strength, with the maximum concrete compressive strengths were obtained at the percentage of aggregate amount of 70% for each w/c-ratio, specimen shape factor and age of testing.Keywords : Compressive strength, aggregate amount, w/c-ratio, specimen shape factor, age of testingAbstrak: Penelitian ini bertujuan untuk mengetahui pengaruh persentase jumlah agregat terhadap kuat tekan pada campuran beton normal dengan Faktor Air Semen (FAS) 0,35; 0,40 dan 0,45, agar diperoleh persentase jumlah agregat dalam campuran beton yang optimal. Benda uji yang digunakan dalam penelitian ini adalah benda uji silinder standar berukuran diameter 150 mm, tinggi 300 mm berjumlah 90 buah dan kubus dengan ukuran 150 x 150 x 150 mm berjumlah 54 buah. Diameter agregat maksimum yang digunakan adalah 25,4 mm dengan tinggi slump rencana 75-100 mm. Variabel pada penelitian ini adalah 3 buah FAS dan 3 variasi persentase jumlah agregat yaitu (60%; 70% dan 80%). Pengujian kuat tekan beton dilakukan pada umur 7 dan 28 hari menggunakan mesin penguji kuat tekan berkapasitas 100 ton. Standar yang digunakan dalam penelitian ini adalah American Concrete Institute (ACI), American Society for Testing and Materials (ASTM), British Standard (BS), dan Standar Nasional Indonesia (SNI). Perencanaan campuran beton dilakukan dengan metode perbandingan berat material. Semen yang digunakan adalah PC (Portland Cement) Tipe I. Untuk mendapatkan data beban dan deformasi pada saat pengujian digunakan portable data logger. Untuk menganalisis pengaruh antar variabel yang digunakan dipilih analisis varian klasifikasi dua arah model efek tetap. Analisis regresi yang digunakan adalah regresi polinomial berganda.Berdasarkan hasil analisis varian ditunjukkan bahwa ada pengaruh yang nyata antara persentase jumlah agregat terhadap kuat tekan beton, dengan kuat tekan beton maksimum diperoleh pada persentase jumlah agregat 70% untuk setiap FAS, faktor bentuk dan umur pengujian.Kata kunci : Kuat tekan, persentase jumlah agregat, FAS, bentuk benda uji dan umur.